2010
DOI: 10.1167/1.3.338
|View full text |Cite
|
Sign up to set email alerts
|

Facial motion can determine facial identity

Abstract: When we speak, laugh or cry our faces move in complex, non-rigid ways. Can such motion patterns influence our perception of facial identity? To explore this issue we took 3D laser scanned heads from the MPI database and animated them using motion sequences captured from different human actors. During an incidental learning phase, observers were exposed to FACE A moving with MOTION A and FACE B moving with MOTION B. Test stimuli consisted of two sets of morphed heads (shaded, no texture) ranging in 10 steps fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…This finding is new and to our knowledge has not been demonstrated previously. Thus, participants were able to use facial motion information exhibited by other‐race faces at encoding as an aid to recognition, as they have been seen to do for same‐race faces (Knappmeyer et al , 2003; Lander & Bruce, 2003; Thornton & Kourtzi, 2002). Explanations of the other‐race effect have suggested that individuating information is ignored with categorical/race‐specific information salient during processing of other‐race faces (Hugenberg, Miller, & Claypool, 2007; Levin, 2000).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This finding is new and to our knowledge has not been demonstrated previously. Thus, participants were able to use facial motion information exhibited by other‐race faces at encoding as an aid to recognition, as they have been seen to do for same‐race faces (Knappmeyer et al , 2003; Lander & Bruce, 2003; Thornton & Kourtzi, 2002). Explanations of the other‐race effect have suggested that individuating information is ignored with categorical/race‐specific information salient during processing of other‐race faces (Hugenberg, Miller, & Claypool, 2007; Levin, 2000).…”
Section: Discussionmentioning
confidence: 81%
“…Interestingly, our moving faces displayed a naturalistic mixture of predominantly non-rigid (talking, expressing) with some limited rigid (head nodding and shaking) movements. Previously, it has been proposed that seeing the face move rigidly provides more depth and structural facial information regarding the identity of the person (Knappmeyer, Thornton, & Bülthoff, 2003). In addition, Lander et al (2007) proposed that viewing a non-rigidly moving face may lead to greater attention being paid to it, which in turn leads to better recognition.…”
Section: Discussionmentioning
confidence: 99%
“…At the time, there were two lines of evidence for the supplemental information hypothesis. The first came from clever experiments that pitted the shape of a face (from a three-dimensional laser-scan head model), which could be manipulated with morphing, against characteristic facial motions projected onto heads that varied in shape (Hill and Johnston, 2001;Knappmeyer, Thornton, and Bülthoff, 2001). These studies provided a pre-requisite demonstration that the facial motion in dynamic identity signatures can bias a face identification decision.…”
Section: Fitting the Psychological Evidence Into The Neural Frameworkmentioning
confidence: 99%
“…The process involves the detection and the interpretation of the muscle movements of the face and as well as the observer's own sensitivity, expectations and mental representations on the observed state [19]. Since the generation of emotions involves sequential movements of faces, people differ in terms of how rapid they recognize the emotion as well as the accurateness [16].…”
Section: Journal Of Childhood and Developmental Disorders Issn 2472-1786mentioning
confidence: 99%